Let's solve the first equation for x:
x + y = 7 ------------------------------------------------------------------------------ Equation 1
x = 7 - y ------------------------------------------------------------------------------ Equation 1A
Now, we substitute Equation 1A into Equation 2 and solve for y:
** This means that we put what ever is x equal to in Equation 1A into the "x" of Equation 2. Then we multiply it out and do algebra to solve for y. SHOWN BELOW: **
y = -2x + 12 ----------------------------------------------------------------------- Equation 2
y = -2(7 - y) + 12
y = -14 +2y + 12
14 - 12 = 2y - y
y = 2
Equaton 1 was:
x + y = 7
We know y = 2, so substituting, we can solve for x:
x + y = 7
x + 2 = 7
x = 7 - 2
x = 5